First Description of a β-Thalassemia Mutation, −86 (C > G) (HBB: c.−136C > G), in a Chinese Family. (2nd November 2015) - He, Sheng; Qin, Qian; Yi, Shang; Zhou, Wanjun; Deng, Jianping; Zheng, Chenguang; Chen, Biyan
Abstract: We present the first description of a Chinese family with a β-thalassemia (β-thal) mutation −86 (C > G) ( HBB : c.−136C > G). This mutation changes the conserved promoter sequence within the proximal CACCC box of the β-globin gene that leads to a phenotype of β + -thal. The β-globin haplotype analysis revealed that the −86 mutation in our case was linked with haplotype I [+ − − − − + +]. This haplotype was commonly found both in the β-thal mutation and the β A gene. Our results suggest that the −86 mutation possibly does not have a distinct origin.